1996
DOI: 10.1056/nejm199601183340316
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis G Infection in Drug Abusers with Chronic Hepatitis C

Abstract: CORRESPONDENCE 191Instructions for Letters to the Editor Letters to the Editor are considered for publication (subject to editing and abridgment) provided they do not contain material that has been submitted or published elsewhere. Please note the following:• Your letter must be typewritten and triple-spaced. • Its text, not including references, must not exceed 400 words (please include a word count). • It must have no more than five references and one figure or table.• It should not be signed by more than th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
87
2

Year Published

1996
1996
1999
1999

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 201 publications
(99 citation statements)
references
References 4 publications
10
87
2
Order By: Relevance
“…The data obtained up to the present indicate that the virus can persistently infect patients on maintenance haemodialysis for 16 years or longer (Masuko et al, 1996), and is transmitted by transfusion and intravenous drugs (Aikawa et al, 1996 ;Linnen et al, 1996 ;Masuko et al, 1996 ;Schmidt et al, 1996). Remarkably, the infection with GBV-C\HGV is prevalent in carriers of HCV (Aikawa et al, 1996 ;Egawa et al, 1996 ;Linnen et al, 1996 ;Masuko et al, 1996), indicating a common route of transmission or a possible synergism of the two viruses. Although persistent infection with GBV-C does not seem to be associated with significant hepatic injuries (Masuko et al, 1996), GBV-C RNA has been reported in some patients with fulminant non-A to E hepatitis (Yoshiba et al, 1995).…”
Section: Introductionmentioning
confidence: 84%
“…The data obtained up to the present indicate that the virus can persistently infect patients on maintenance haemodialysis for 16 years or longer (Masuko et al, 1996), and is transmitted by transfusion and intravenous drugs (Aikawa et al, 1996 ;Linnen et al, 1996 ;Masuko et al, 1996 ;Schmidt et al, 1996). Remarkably, the infection with GBV-C\HGV is prevalent in carriers of HCV (Aikawa et al, 1996 ;Egawa et al, 1996 ;Linnen et al, 1996 ;Masuko et al, 1996), indicating a common route of transmission or a possible synergism of the two viruses. Although persistent infection with GBV-C does not seem to be associated with significant hepatic injuries (Masuko et al, 1996), GBV-C RNA has been reported in some patients with fulminant non-A to E hepatitis (Yoshiba et al, 1995).…”
Section: Introductionmentioning
confidence: 84%
“…Fax: +81-52-852-0849. E-mail : mizokami@med.nagoya-cu.ac.jp venous drug users [3,4]. Comparison of the nucleotide and the deduced amino acid sequences showed good homology between these viruses.…”
Section: Introductionmentioning
confidence: 98%
“…[1][2][3] The virus has been shown to be transmitted via parenterally administered blood or blood products. 4 In Japan the prevalence is estimated at 1.1% in voluntary donors without any markers of HCV or HBV infection. 5 There are many factors and pathologic conditions known to cause liver dysfunction after BMT, including drug-related toxicity, hepatic veno-occlusive disease (VOD), GVHD and viral hepatitis, due to infection with cytomegalovirus, herpes simplex virus, varicella zoster, adenovirus, hepatitis C virus (HCV) and hepatitis B virus (HBV).…”
mentioning
confidence: 99%